THE GREAT GATSBY - Fitzgerald, F. Scott, 1896-1940.; Connolly, Sean; Kalda, Sam (Berkshire, U.K. : Baker Street Press, 2018)
Nick Carraway's mysterious neighbour Gatsby gazes across the dark bay at a distant green light...As the summer unfolds, Nick is drawn into Gatsby's world of luxury cars, speedboats and extravagant parties.
Keywords: Children's stories, English; English fiction